Abuse of Drugs for Medicine (Study of Decision Number 111/PID.SUS/2017/PNSAG) - Husni Akhmad Husein; Muchamad Iksan (Proceeding International Conference Restructuring and Transforming Law, 2024)
Even after several decades, we still confront many issues today. Narcotics are one of the topics that have generated controversy up to this point. These days, it is inextricably linked to the global elite's influence over national regulations. The original purpose of narcotics regulations, which had nothing to do with health or medicine, was to control the spice trade. Eventually, many nations adopted the created regulations as the basis for their drug prohibition laws. This subsequently turned into a contentious issue because some drugs have therapeutic uses, and Indonesia is known to be among the nations with the strongest anti-drug policies. Even though now something that has benefits in Islam certainly has the opportunity to be used, because it is the basis of Islam which gives Grace to the whole world. The creation of narcotics is not without reason, it does have drawbacks if used on the wrong person and not only on drugs but on all things. This study will provide a brief overview of narcotics in the medical world. concise, and clear. In this study, the author will also use a normative legal research method which will analyze the existing problems through legal and library materials. And specifically to the case in the decision Number 111 / Pid.Sus / 2017 / PN.Sag which contributed to taking someone's life.